2017
DOI: 10.1109/tfuzz.2016.2574906
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Approaches to Option Price Modeling

Abstract: The aim of this paper is to review the literature that has addressed direct and inverse problems in option pricing in a fuzzy setting. In a direct problem, the stochastic process for the underlying asset is assumed and the option prices are derived by no-arbitrage or equilibrium conditions. In an inverse problem, the option prices are taken as given and used to infer the underlying asset process. Models are divided into discrete-time and continuous-time ones. Special attention is paid to real options, a partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…The model of fuzzy programming is used to specify the portfolio, which meets the investors´ requirements. Incorporation of fuzzy approaches to option price modelling is explained in the studies of Munoz et al (2013) and Muzzioli and De Beats (2017). The analysis of investors´ expectations of financial development is depicted in the study of Barbera et al (2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The model of fuzzy programming is used to specify the portfolio, which meets the investors´ requirements. Incorporation of fuzzy approaches to option price modelling is explained in the studies of Munoz et al (2013) and Muzzioli and De Beats (2017). The analysis of investors´ expectations of financial development is depicted in the study of Barbera et al (2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Under long-term uncertainty, the ability to defer reinforcement is more valuable than that under deterministic scenarios [40]. Because the defer option can provide planning flexibility in response to various future conditions [41]. Since bus 13 advances the reinforcement of L19, L20 and L28 significantly, it kills the option to wait for new information and productively invest in the future.…”
Section: Performance Comparisonmentioning
confidence: 99%
“…Moving to the field of financial asset valuation, one of the areas in which fuzzy logic has been widely used is in options pricing. Muzzioli and De Baets [50], in a comprehensive literature review on the topic, identified that the majority of papers using fuzzy logic for option pricing have addressed the direct problem of pricing in both discrete and continuous time settings. Several articles have shown that fuzzy logic is suitable for identifying the market value of complex instruments, such as derivatives [51][52][53].…”
Section: Systematic Analysismentioning
confidence: 99%